2022
DOI: 10.3354/esr01182
|View full text |Cite
|
Sign up to set email alerts
|

Association of ocean macroplastic debris with stranded sea turtles in the Central Gulf of Thailand

Abstract: The impact of macroplastic debris (>5 mm) on marine life is a global concern but has rarely been investigated in Thailand. This study investigated the relationship between stranded sea turtles and macroplastics in the Central Gulf of Thailand. Records of stranded turtles (n = 388) from 2017-2020 were analysed retrospectively to determine their interaction with macroplastics. In addition, macroplastics collected from the gastrointestinal (GI) tracts of 30 dead stranded turtles and 13 beaches (along a 100 m t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…Furthermore, sea turtle bycatch also influences the stranding rate [ 19 , 20 ]. Previous studies in Thailand reported that anthropogenic factors, such as plastic waste or fishery activities, were important factors that led to sea turtle stranding [ 12 , 21 ]. In this regard, further research is needed to determine the factor with the greatest effect on sea turtle stranding in Thailand.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, sea turtle bycatch also influences the stranding rate [ 19 , 20 ]. Previous studies in Thailand reported that anthropogenic factors, such as plastic waste or fishery activities, were important factors that led to sea turtle stranding [ 12 , 21 ]. In this regard, further research is needed to determine the factor with the greatest effect on sea turtle stranding in Thailand.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, fishing nets were reported to be associated with the stranding of sea turtles in the Gulf of Thailand. Researchers have also found macroplastic debris in the gastrointestinal tracts of stranded sea turtles [ 12 ]. In other countries, marine mammals have become stranded owing to illness, fisheries activities, and environmental changes [ 13 ], while sea turtle strandings have been reported to be related to anthropogenic factors and illness [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…(For interpretation of the references to colour in this figure legend, the reader is referred to the web version of this article.) Investigation of marine vertebrate strandings provides scientists with opportunities to explore the impacts of plastic pollution (Abreo et al, 2019a;Lusher et al, 2018;Nelms et al, 2019;Prampramote et al, 2022). Entanglement can be established through visual observations of animals using images from social media, for example (e.g.…”
Section: Publicationsmentioning
confidence: 99%
“…It transpired through the expert elicitation that cases exist as unpublished for far more species than is currently described in the published literature, although new publications filling in those gaps have emerged since our literature search was performed (e.g. Gajanur and Jaafar, 2022;Ng et al, 2022;Prampramote et al, 2022;Yong et al, 2021). Green and leatherback turtles were the only two species for which published cases of both entanglement and ingestion were available from the SE Asian countries.…”
Section: Taxonomic Groupsmentioning
confidence: 99%
“…It has been estimated that 10% of the mismanaged plastic waste ends up in the marine environment where it will persist and accumulate over the coming years [7]. The large fragments of plastic debris found in the environment are termed macroplastics [8], and they are known to harm turtles and sea birds via entanglement [9,10].…”
Section: Introductionmentioning
confidence: 99%